Paparan toluen di udara ambien industri percetakan terhadap kadar hippuric acid urin pada pekerja industri percetakan di kota Medan tahun 2018 - Mutiara Nauli; Taufik Ashar; Rahayu Lubis (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Toluene exposure and urine hippuric acid level in printing workers in Medan in 2018Purpose: The printing industry has been one of the growing industries. The printing industry in Indonesia in 2011 is estimated to reach 4.7 percent or higher than the average world growth, which is only 1.6 percent. The production and printing services needs in Indonesia are significantly increasing. Industrial processes that use labor, especially those related to using chemicals in the production process, will be at high risk of potential hazards. According to the Ministry of Industry and Trade, 45 industries use hazardous materials, one of which is the printing industry. This study aims to analyze exposure to toluene through urine hippuric acid levels in the printing industry workers. Methods: This research is a quantitative observational analytic study using a cross-sectional design conducted from March to July 2018. The sample of this study is 50 respondents located in 6 printing industries in Medan City. Most of the respondents are males, which is 38 people (76%). Results: The average value of ambient air toluene exposure in 6 printing companies was 6.97 ppm, much lower than the threshold value of 50 ppm, and the average hippuric acid level of printing employees is 143.5 mg/g creatinine, which is far from the threshold value of 1600 mg/g creatinine. There is a correlation between sex with hippuric acid levels (p <0.05). Conclusions: Printing business owners should monitor their employees' health periodically. The Health Ministry also needs to regulate the protection of workers from toluene. To reduce toluene exposure, printing industry owners should equip their employees with personal protective equipment and manage better office hours, a day off, and furlough.